ETLINGERA COMOSA, A NEW SPECIES (ZINGIBERACEAE: ALPINIOIDEAE) FROM CENTRAL SULAWESI - Marlina Ardiyani; Wisnu Handoyo Ardi; Prima Wahyu Kusuma Hutabarat; Axel Dalberg Poulsen (Research Center for Biology, 2021)
ARDIYANI, M., ARDI, W. H., HUTABARAT, P. W. K. & POULSEN, A. D. 2021. Etlingera comosa, a new species (Zingiberaceae: Alpinioidea) from Central Sulawesi. Reinwardtia 20(2): 63−68. — Etlingera comosa Ardiyani & Ardi, a new and unusual species from Tentena, Central Sulawesi exhibiting terrestrial as well as epiphytic habit is described here. It is compared to the morphologically closest Etlingera sublimata A.D.Poulsen, but differs in having tufted sheath, bilobed and asymmetric ligule, loose peduncular bracts, densely pubescent fertile bracts and longer filament. Colour plates, notes on its conservation status and DNA barcode data for the new species are also provided.